Differential comparison of genotoxic effects of aristolochic acid I and II in human cells by the mass spectroscopic quantification of γ-H2AX. (June 2022) - Qu, Minmin; Xu, Hua; Chen, Jia; Xu, Bin; Li, Zhi; Ma, Bo; Guo, Lei; Ye, Qinong; Xie, Jianwei
Abstract: Aristolochic acids (AAs) are known to be the potent genotoxic carcinogens, of which aristolochic acid I (AAI) and aristolochic acid II (AAII) are the two representative compounds. As the carcinogenic risk of herbs containing AAs is a global health issue, quantitative evaluation of genotoxicity is needed for the risk assessment of AAs. γ-H2AX, which is an acknowledged attractive bifunctional biomarker for simultaneously reflect the DNA damage response and repair, was used to quantitatively determine the DNA damage and repair properties of AAI and AAII in human cell lines, based on our previously developed mass spectrometry method. Results indicated that both AAI and AAII could increase the level of γ-H2AX in cells in a concentration-dependent manner, and the increased level of γ-H2AX induced by AAI was relatively higher than that induced by AAII. Time-effect curves showed that the change tendency of the proportion of γ-H2AX was obviously different in the later period, particularly afterwards 8 h post exposure. Additionally, AAI and AAII induced an opposite change of expression levels of DNA damage repair-associated proteins (ERCC1 and p53) in HepG2 cells, revealing their distinct molecular mechanisms. Findings of the present study are helpful for understanding the genotoxicity mechanism of AAI and AAII. Highlights: We used γ-H2AX for quantitative evaluation of the difference in DNA damage and repair induced by AAI and AAII. The concentration- and time-dependent changes between AAs and γ-H2AX in three types of human cell lines were monitored. We explored the expression levels of ERCC1 and p53 proteins after exposing cells to AAI and AAII. The work is valuable for understanding the genotoxicity mechanism of AAs.